The Effectiveness of Student Worksheet to Improve Metacognitive Abilities on Factors That Affect the Reaction Rate Through an Inquiry Learning Model - Desi Dika Sari; Suyono; Antina Delhita (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Metacognitive ability is part of higher order thinking so it has an important role in strengthening the critical and creative thinking dimensions in the Profil Pelajar Pancasila (P3). This study aims to develop a learner activity sheet to improve metacognitive skills on the material of factors that affect the reaction rate through an effective inquiry learning model used to improve metacognitive skills. This research uses the ADDIE (Analysis, Design, Develop, Implement, Evaluate) research design which is limited to the develop stage. Based on the results of the pilot implementation, it was found that the student worksheet developed was effective based on the results of the metacognitive ability test which showed a p-value < 0,05 so that H0 was rejected and H1 was accepted which meant that there was a significant increase in value after learning using the developed student worksheet.